Peculiarities of the babesiosis infection influence to nonlinear mice stomach structure (experimental and morphological investigation. - Pokhil, S; Torianik, I; Tymchenko, O; Chigirinska, N; Kostyria, I; Boletch’ka, T (Annals of Mechnikov’s Institute, 2020)
The babesias are one of the most ubiquitous and widespread blood parasites in the worldbased on numbers and distribution of species in animals, second only to the trypanosomes . They generally have two classes of hosts, an invertebrate and a vertebrate host. The maintenance of Babesia spp. Is dependent on both hosts; the specific tick vector must feed on a vertebrate reservoir that is competante in maintaining the Babesia organisms in an infectious state. Therefore, B. microti presents itself as an emerging zoonosis only in areas where there is a primary competent reservoir. The first documented case of babesiosis in humans was in 1957 . A splenectomized farmer in Yugoslavia was diagnosed with a B. bovis infection. But now most cases of babesial infections in humans have been asquired in temperate regions of the USA and Europe. That a tick-transmitted protozoan parasite, one of the causative agents of piroplasmosis (babesiosis). The disease is characterized by sings of malaise, inappetence, fever, hemolytic anemia and hemoglobinuria. The parasite has a wide distribution and occurs on all continents, except Australia. The life cycle of the parasite in animals organism (equine hosts, traveling dogs, cats) comprises two intracellular stages: sporozoites innoculated by infected ticks develop into schizonts within lymphocytes where they maltiply and subsequently transform into microzoites, which then invide erythrocytes. Purpose of the experiment’s to study the influence of the babesious infection to nonliner female mice stomach structure. Materials and methods. The examinational material of this investigations are the female nonliner controle intact miсe of the 4-6-week-old (n=15) and such paterns, which were with the babesious infection (n=45). For all of examinational animals groups were used macroscopic and hystological methods. Macroscopic analysis was included organoleptic, biomechanical, microtopographical methods of investigations (external status, volum, size, syn-, holo-, skeletotopy). Microscopic examination was carried out in a traditional way. Bits of the material were removed, washed, fixed in 12 % formalaldehyde, subjected to postfixation and dehydrated (providing have been worked in standart algoritm’s). Sections were contrasted by hematoxsilin and eosin, azur and eosin, Brashe, sudan IIIsudan IV, analysed under a microscope LOMU (LOMO, Russia): x 300; x400; 1350 and photographed with a digital camera “Canon EOS-3000”. Results. Clinically disease manifestations of babesiosis are caused by the asexual reproductive stage of the organism in digestive system organs, erythrocytes of the host and the subsequent lysis of same host cells. Consequently, there is a very broad clinical spectrum which is probably directly reflective of the level of parasitemia in the blood. Morphologically: gastrical tunics (mucosal, muscular, serosal) of the control groupe animals are very visible and norm. The changes of abdominal microthopography it was not found. Megalia, oedema, hyper-, atrophia, inflammatory processus are absent. It was found out that a pronounced structuralfunctional changes of stomach, submucosal lymphoid tissues and endothelium of gastrical microvessels took place during first days of the observation of animals with the babesiosis. The above regression was attributed to development of thrombosis, stasis, trophic changes, development of destruction and necrosis. Characteristic morphological signs consisted of changes in the nucleus/cytoplasm ratio of cells, development of lympholeucocellular, lympho-hystiocellular infiltration, proliferation, vacuolization of cytoplasm, caryorexis, transformation of chromatin, appearance of megakaryocytes in the bloodstream and their markedly increased count. Conclusions: macro- and microscopic changes in the stomach of 4-6-week-old nonliner female mice (with the babesiosis) were with the phase character, have been depended upon terms of the début of babesiosis and consisted in destruction of stomach structural components, gastric microvessels roofs.